The image of Iceland. Actual summer visitors image of Iceland as a travel destination - Gunnar Magnússon 1978- (2008)
The image of tourist destinations is important, because it influences both the decisions tourists make about what destination to visit and the level of satisfaction tourists have, based on the actual experience at the destination. At the international level, destinations often compete on nothing more than the image held in the minds of potential travelers. Therefore, marketers of tourist destinations spend money, time and effort to create the right favorable image to guide prospective travelers in their decision to visit or re-visit their destinations. The goal of this research was to investigate the image actual travelers in Iceland during the summer months have of the country as a tourist destination. The goal was also to examine if Iceland, the Faroe Islands and Greenland can be positioned together in tourist markets as one area, since it has been established that areas that pool their resource can have more marketing power if they cooperate than if they use resources separately. Two surveys were constructed and administered. The first survey (unstructured) measured the holistic image of Iceland. The results from this survey were coded with a qualitative methodology. The second survey (structured) measured the attribute image of Iceland in comparison with five other countries, Norway, Scotland, Greenland, Finland and the Faroe Islands. The results from the second survey were put into a statistical program and analyzed with perceptual maps. Results from the unstructured survey indicate that travelers have the strongest holistic image of Iceland as a scenic nature destination. Results from the structured survey indicate that the image tourist in general have of Iceland as a tourist destination is a country that is a safe place to visit, offers opportunity for adventure, is friendly and hospitable and possesses scenic and natural beauty. Results also indicate that people have a strong and clear image of Iceland. Image differences were recognized between nationalities and age groups, between first time and repeat ...